Prevalence of Scoliosis Among Primary and Middle School Students in Mainland China: A Systematic Review and Meta-analysis. Issue 1 (1st January 2015) - Zhang, Hongqi; Guo, Chaofeng; Tang, Mingxing; Liu, Shaohua; Li, Jinsong; Guo, Qiang; Chen, Lizhang; Zhu, Yong; Zhao, Shushan
Abstract : Study Design: Systematic review and meta-analysis of published prevalence of scoliosis among primary and middle school students in Mainland China. Objective: To evaluate the prevalence of scoliosis among primary and middle school students in Mainland China. Summary of Background Data: There is substantial uncertainty regarding the prevalence of scoliosis in Mainland China among the primary and middle school students. We conducted a systematic review aiming to describe the prevalence of scoliosis in Mainland China. Methods: We systematically reviewed the published epidemiological studies or reports on the prevalence of scoliosis in Chinese cities. Scopus, PubMed, WanFang Database, CNKI, China National Science and Technology Digital Library, and WeiPu Database were searched for studies reporting a prevalence estimate for scoliosis in primary and middle school students. Meta-analyses were performed to estimate the pooled prevalence of scoliosis by STATA 12.0. Subgroup analyses were conducted according to the sex, age, and geographical area. Results: A total of 38 articles, including 697, 043 patients, were eligible for inclusion in this review. Meta-analyses revealed the prevalence of scoliosis to be 1.02% (95% [confidence interval] CI, 0.85–1.18) among the primary and middle school students in Mainland China. The female to male ratio was 1.54 (95% CI, 1.35–1.74; P < 0.001). According to the subgroup analysis by different ages, the prevalence of scoliosis increased from 0.73% (95% CI, 0.55–0.90) to 1.14% (95% CI, 0.86–1.42). Conclusion: Meta-analyses showed that the prevalence of scoliosis in Mainland China was 1.02% among the primary and middle school students. The prevalence of scoliosis in females was higher than in males and the ratio was 1.54. As they grew older, the prevalence of scoliosis increased in the students. Level of Evidence: 2 Abstract : Supplemental Digital Content is Available in the Text.There is substantial uncertainty regarding the prevalence of scoliosis in Mainland China. We systematically reviewed the published epidemiological studies or reports. Meta-analyses revealed the prevalence to be 1.02%. The female to male ratio was 1.54.